From corporate social responsibility to organizational resilience: the role of sustainability control systems and governance heterogeneity - Latif, Badar; Elbanna, Said; Hanan, Abdul; Roh, Taewoo (John Wiley and Sons Ltd, 2026)
Corporate social responsibility (CSR) has increasingly been recognized as a strategic lever for enhancing organizational resilience. Although CSR literature is abundant, prior research has not fully explained how distinct CSR types, such as altruistic, promotional, and value-creating, influence organizational resilience through sustainability control systems (SCSs). Consequently, the mechanisms linking these CSR types to resilience remain insufficiently understood. This study, grounded in signaling theory, addresses the research gap by empirically investigating the influence of distinct CSR types on organizational resilience and examining the mediating role of SCS, as well as the moderating effect of governance heterogeneity in this relationship. Data were collected from 121 large enterprises in Pakistan and analyzed using structural equation modeling to test the proposed hypotheses. The findings reveal that (1) CSR types positively and directly contribute to organizational resilience, (2) SCS significantly mediates the relationship between CSR types and organizational resilience, and (3) governance heterogeneity negatively moderates the positive effect of SCS on organizational resilience. These results highlight the strategic value of adopting targeted CSR practices and implementing effective sustainability controls to strengthen organizational resilience.